Trehalose alleviates nephropathy in focal segmental glomerulosclerosis via the upregulation of the WT-1/EZH2 pathway - Al-Asmakh, Maha; Riyami, Marwa AL; Al Marbuii, Miytha; Al Sinawi, Shadia; Al-Badi, Suaad; Ismaili, Faisal AL; AlKharusi, Amira; Zadjali, Razan; Alharthi, Zaina; Al Mashrafi, Sara; Al Breiki, Razan; Al-Hashmi, Sulaiman; et al. (Frontiers in Pharmacology, 2025)
IntroductionFocal segmental glomerulosclerosis (FSGS) is a serious disease that culminates in kidney failure. Today, FSGS is diagnosed histologically as a progressive scarring of the glomeruli due to gradual loss or damage of the podocyte layer, making it one of the main targets of FSGS therapeutic approaches. However, given that podocytes are terminally differentiated, post mitotic epithelial cells with limited proliferative capacity, they are considered one of the most vulnerable components of the glomeruli.Aim and MethodsWe herein investigated the effect of trehalose, a naturally occurring sugar with low toxicity and high stability, on kidney function using a murine model of adriamycin‐induced nephropathy.ResultsBased on our data, trehalose administration improved proteinuria in mice with FSGS compared to those without FSGS induction (24 h urine protein of 0.30±0.06 versus 0.55±0.08, p-value<0.05, and urine protein to creatinine ratio of 0.78±0.25 versus 1.56±0.17, p-value<0.05, respectively this is accompanied by reduced fibrosis and podocyte damage. Significant reduction in collagen deposition in glomeruli observed in mice treated with trehalose, P-value<0.01 and significant reduction in glomerular basement membrane thickness, P-value<0.001. Moreover, trehalose intake is associated with higher mature podocyte markers at gene and protein expression levels, Nphs1, Nphs2 and Synpo. These favorable effects seem to be mediated mainly via increased WT-1/EZH2 signaling, which is a key pathway in maintaining normal podocyte function and growth. These effects were also observed in the downstream signaling pathway with lower expression of Mmp-7 and Catenin b1 gene expression (p-value<0.05 and <0.01, respectively).ConclusionOur findings suggest that trehalose could be a promising therapeutic agent for FSGS, nevertheless, more studies are necessary to confirm our findings and evaluate trehalose efficacy in clinical settings.